Impact of bispectral index monitoring on critical incidents rate in high-risk patients: a randomised controlled trial - N. V. Trembach (Кубанский научный медицинский вестник, 2022)
Background. The likelihood of intraoperative critical incidents depends largely on reﬂex control of the cardiorespiratory system that is often susceptible to chronic pathology. The reﬂex suppression may link to the depth of anaesthesia, making the latter monitoring particularly important at higher hypotension risks and their patient predisposition.Objectives. A study of the effect of bispectral index anaesthesia monitoring on critical incidents (CIs) rate in high-risk abdominal surgery patients.Methods. A randomised controlled trial enrolled 80 high-risk and 80 low-risk patients. Each cohort randomly allocated patients between subcohorts (by 40 people): 1 — anaesthesia rendered to maintain a 40–60 bispectral index (treatment cohort), 2 — by clinical values and anaesthetic level control in exhaled gas (control cohort), intraoperative control of anaesthetic requirement, bispectral index and critical incidents.Results. A critical incidents rate analysis in high-risk patients showed a lower rate in the bispectral index anaesthesia control cohort. Total 127 critical incidents were registered in 53 patients. The analysis revealed fewer CIs for objective sedation depth monitoring, 45% patients of treatment cohort vs. 87.5% in control. Signiﬁcantly fewer (by half) patients exhibited hypotension in the treatment cohort, with lower (4-fold) rates of arrhythmia, bradycardia and general respiratory CIs. Anaesthetic doses and bispectral indices at anaesthesia stages were signiﬁcantly lower in the treatment cohort as well.Conclusion. Objective anaesthesia depth monitoring in high-risk patients reduces the rates of haemodynamic incidents during anaesthesia maintenance and respiratory incidents at arousal due to prevention of excessive anaesthetic depth.